A Randomized Clinical Trial Comparing Artesunate/Amodiaquine and Coartem in Treatment of Uncomplicated Malaria in Pregnancy in Mulago Hospital - Kimera, Charles Lukanga (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2019)
BACKGROUND: The therapeutic efficacy and safety of artesunate plus amodiaquine and artemether/lumefantrine were assessed in Mulago hospital, Kampala, Uganda, an area with high levels of Plasmodium falciparum resistance to chloroquine and sulphadoxine-pyrimethamine. MATERIALS AND METHODS: A total of 369 pregnant mothers beyond the first trimester (>12 weeks) and less than 37 weeks of gestation with signs and symptoms of malaria were screened for malaria parasites. Of these, 109 had uncomplicated malaria infection with parasite density 200 to 200,000 parasites/?L and were enrolled following informed consent. Eligible pregnant mothers were randomly assigned to receive either a 3-day course of Coartem (Artemether 20mgs/ Lumefantrine 200mgs) 4 tablets twice a day 12 hourly on days 0, 1 and 2; or Artesunate/Amodiaquine on days 0, 1 and 2 (4tablets of Artesunate plus 4 tablets of Amodiaquine once a day). The Coartem arm had 55 participants while the Artesunat/Amodiaquine (DUACT) arm had 54 participants. Patients were followed up with clinical and laboratory assessments until day 14. RESULTS: The clinical and parasitological response between Coarten (artemether-lumefantrine) and artesunate+amodiaquine (DUACT) in the treatment of uncomplicated malaria in pregnant mothers were statistically similar. The side effects for the two treatment arms were also statistically similar. CONCLUSION: Artemether-lumenfantrine (coartem) and artesunate plus amodiaquine (DUACT) had high and similar cure rates and tolerability among pregnant mothers in Mulago Hospital, Uganda.